La investigación formativa como estrategia de aprendizaje de Biología Animal “vertebrados” con los estudiantes de cuarto semestre de la carrera de Pedagogía en Química y Biología, en el periodo mayo 2021 – octubre 2021 - Jara Andino, Jennifer Nicole (2022)
Formative Research has become a topic of interest for training research pedagogues in the educational field. The importance acquired is mainly related to the university's mission of training professionals trained to teach and learn in the activities of scientific and pedagogical Research, so the Research had as a general objective to propose formative Research as a learning strategy for the subject of Animal Biology with the theme of "Vertebrates" with the fourth-semester students of the Pedagogy in Chemistry and Biology. The work was carried out with a quantitative, non- experimental design, descriptive, basic, bibliographic, and field approach. It focused on an intentional sample of 33 students. The survey technique was used to collect the necessary data with its questionnaire instrument made in Google Forms, consisting of 13 questions with their respective indicators. From all the data and information collected, it was concluded that formative Research is essential for the student since it helps in the learning process, allowing it to develop its criticality and contributing to reflection. Therefore, teachers and students are recommended to involve and use formative Research as classroom projects to encourage the development of the animal biology subject "Vertebrates"